Comparison of cloth and superabsorbent paper diapers for preventing diaper dermatitis. - Oranje, A.P.; de Waard-van der Spek, F.B. (European Journal of Pediatric Dermatology, 2018)
Superabsorbent diapers* contain an absorbent gelling material (AGM), by which the skin wetness in the diapered area is decreased. These diapers prevent the mixing of urine and faeces more efficiently than cloth diapers and paper diapers without AGM. This was demonstrated in different clinical studies. Superabsorbent diapers are superior to all other types of diapers for maintaining the skin condition well. The newly developed and improved cotton panty diapers also fail to match the superabsorbent paper diapers. Another advantage of the superabsorbent paper diapers with a barrier leg-cuff (extra closure at the leg) over the cloth diaper and overpants was reported recently. The use of superabsorbent paper diapers also decreased fecal contamination at day care centers. Therefore it might help to control enteric diseases. A similar effect, however, could also be achieved by using overclothes over either type of diapers (cloth or paper disposable). No allergic or adverse reactions were noticed with AGM diapers in more than 5 years of world-wide use. This underlines the safety profile described in the toxicological tests.